Five Padua days on muscle and mobility medicine (2024Pdm3), Padua, Italy - Sandra Zampieri; Ines Bersch; Piera Smeriglio; Elena Barbieri; Massimo Ganassi; Christiaan Leeuwenburg; Riccardo Rosati; Paolo Gargiulo; Amber Pond; H. Lee Sweeney; Ugo Carraro (PAGEPress Publications, 2023)
At the end of the 2023 Padua Days of Muscle and Mobility Medicine the next year's meeting was scheduled from 27 February to 2 March 2024 (2024Pdm3). During the summer and autumn the program was confirmed with Scientific Sessions that will take place over five days, starting in the afternoon of February 27, 2024 at the Conference Room of the Hotel Petrarca, Thermae of Euganean Hills (Padua), Italy. As usual, the next day will be spent in Padua, in this occasion at the San Luca Hall of the Santa Giustina monastery in Prato della Valle, Padua, Italy. Collected during Autumn 2023, many more titles and abstracts than expected were submitted, forcing the organization of parallel sessions both on March 1 and March 2 2024 confirming attractiveness of the 2024 Pdm3. The five days will include oral presentations of scientists and clinicians from Argentina, Austria, Belgium, Brazil, Canada, Denmark, Egypt, France, Germany, Iceland, Ireland, Italy, Romania, Russia, Slovenia, Switzerland, UK and USA. Together with the preliminary Program at December 1, 2023, the early submitted Abstracts is e-published in this Issue 33 (4) 2023 of the European Journal of Translational Myology (EJTM). You are invited to join, submitting your Last Minute Abstracts to ugo.carraro@unipd.it by February 1, 2024. Furthermore, with the more generous deadline of May 20, 2024, submit please "Communications" to the European Journal of Translational Myology (Clarivate's ESCI Impact factor 2.2; SCOPUS Cite Score: 3.2). See you soon at the Hotel Petrarca in Montegrotto Terme, Padua, on February 27, 2024, but the complete program can be followed from home via zoom connection.